Performance of disabled swimmers in protocols or tests and competitions: a systematic review and meta-analysis - Feitosa, W. G.; de Assis Correia, R.; Barbosa, T. M.; de Souza Castro, F. A. (Sports Biomechanics, 2022)
Biomechanical and coordination measurements are useful tools to assess swimming performance. Regarding Paralympic swimming, function and technique make these measurements complex. The aim of this study was to perform a systematic review of studies on biomechanics, coordination and performance in disabled swimmers following swimming protocols and in competitions. Data sources: PubMed, EMBASE, ISI Web of Knowledge, SPORTDiscus and Academic Search Premier. We selected complete studies, published until June 2018. Eighteen studies satisfied the inclusion criteria and were selected for qualitative analysis; nine of these were included in the meta-analysis. Swimming speed and stroke length increase with less impact of physical, visual and intellectual impairment on performing specific swimming tasks. Stroke rate is more stable all through the sport classes than both swimming speed and stroke length. Most physically disabled swimmers adopt the catch-up coordination model. Stroke rate is responsible for most of the intracycle velocity variation in swimmers with amputations or malformations of the upper limbs. No study was found on propulsive efficiency. Swimmers with disabilities should work more on stroke rate, with small decreases in stroke length to achieve higher swimming speeds, lower swim coordination index (more negative) and lower speed variations.